PNPLA3 rs738409 I748M is associated with steatohepatitis in 434 non‐obese subjects with hepatitis C. Issue 10 (20th March 2015) - Petta, S.; Vanni, E.; Bugianesi, E.; Rosso, C.; Cabibi, D.; Cammà, C.; Di Marco, V.; Eslam, M.; Grimaudo, S.; Macaluso, F. S.; McLeod, D.; Pipitone, R. M.; et al.
Summary Background The PNPLA3/Adiponutrin rs738409 C/G single nucleotide polymorphism is associated with the severity of steatosis, steatohepatitis and fibrosis in patients with non‐alcoholic fatty liver disease, as well as the severity of steatosis and fibrosis in patients with chronic hepatitis C (CHC). Aim To test in genotype 1(G1)‐CHC patients, the putative association between the PNPLA3 variant and histological features of steatohepatitis, as well as their impact on the severity of fibrosis. Methods Four hundred and thirty‐four consecutively biopsied Caucasian G1‐CHC patients were genotyped for PNPLA3 rs738409, its effect evaluated by using an additive model. Histological features of steatohepatitis in CHC were assessed using the Bedossa classification. Hepatic expression of PNPLA3 mRNA was evaluated in 63 patients. Results The prevalence of steatohepatitis increased from 16.5% in patients with PNPLA3 CC, to 23.2% in CG and 29.2% in the GG genotype (P = 0.02). By multiple logistic regression, PNPLA3 genotype (OR 1.54, 95% CI 1.03–2.30, P = 0.03), together with age (OR 1.03, 95% CI 1.00–1.05, P = 0.02), BMI ≥ 30 (OR 2.06, 95% CI 1.04–4.10, P = 0.03) and homoeostasis model assessment (HOMA, OR 1.18, 95% CI 1.04–1.32, P = 0.006) were independently linked to steatohepatitis. When stratifying for obesity, PNPLA3 was associated with NASH in non‐obese patients only (12.0% in CC vs. 18.3% in CG vs. 27.3% in GG, P = 0.01), including after correction for metabolic confounders (OR 2.06, 95% CI 1.26–3.36, P = 0.004). We showed an independent association between steatohepatitis (OR 2.05, 95% CI 1.05–4.02, P = 0.003) and severe fibrosis. Higher liver PNPLA3 mRNA was associated both with the severity of steatosis (adjusted P = 0.03) and steatohepatitis after adjusting for gender, age, BMI and HOMA (P = 0.002). Conclusion In patients with genotype 1 hepatitis C, the PNPLA3 G variant is associated with a higher risk of steatosis severity and steatohepatitis, particularly among non‐obese subjects.